2009 2nd International Symposium on Applied Sciences in Biomedical and Communication Technologies 2009
DOI: 10.1109/isabel.2009.5373673
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a BCI system using the GA tehnique

Abstract: Abstract-This paper, that continues a previous research, has as primer goal the improvement of a brain computer interface (BCI) system that uses a new features extracting method named Adaptive Nonlinear Amplitude and Phase Process (ANAPP). The ANAPP method models the EEG signals as a combination of five a priori "spontaneous cortical oscillations" whose amplitudes and phases are established using an adaptive algorithm. While in a series of previous researches [1], [2] the amplitude features of the model were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Since in each iteration the achieved informedness result on the validation set throughout the population is used as a reference for the selection of a sub-set of population for the next generation (except in random search), it can be concluded that the learning inside the used evolutionary methods is influenced by the validation set. Despite the fact that such results are reported in several studies [17], [18], [19], and [20] it is possible to consider this as a case of contamination between the training and evaluation sets. To avoid such scenario, a final evaluation step is conducted in which the training and testing sets are used to evaluate the results using Sigmoid ELM (the classifier that the EA approaches outcomes are customized on) and two alternative classifiers (Polynomial SVM and Perceptron).…”
Section: Resultsmentioning
confidence: 91%
“…Since in each iteration the achieved informedness result on the validation set throughout the population is used as a reference for the selection of a sub-set of population for the next generation (except in random search), it can be concluded that the learning inside the used evolutionary methods is influenced by the validation set. Despite the fact that such results are reported in several studies [17], [18], [19], and [20] it is possible to consider this as a case of contamination between the training and evaluation sets. To avoid such scenario, a final evaluation step is conducted in which the training and testing sets are used to evaluate the results using Sigmoid ELM (the classifier that the EA approaches outcomes are customized on) and two alternative classifiers (Polynomial SVM and Perceptron).…”
Section: Resultsmentioning
confidence: 91%
“…It also focuses on its importance on the rehabilitation of neurological disorders such as attention deficit/hyperactivity disorder. The classification algorithm used in Dobrea and Dobrea (2009) includes genetic algorithm-based ideology resulting in a better classification result and a faster BCI system. Khorshidtalab and Salami (2011) is an abstract review of the various classifications and feature extraction methods used in real-time EEG signal processing.…”
Section: Prior Workmentioning
confidence: 99%
“…This cost had to be minimized by the GA. Two of` the main parameters of the GA, with an important impact on both -the convergence time to a solution and the quality of that solution -, are the population size and the crossover operator. In our case, related with this particular problem and based on a previous experience [7], a population of 15 chromosomes was used. The second parameter was managed in this analysis based on three different trials, with three different types of crossover operators.…”
Section: B Classification Of Eeg Features With Individual Spectral Bmentioning
confidence: 99%